The Therapeutic Function of Metaphor: the Case of Emotions in the Croatian Public Discourse - Stanojević, Mateusz-Milan; Čičin-Šain, Višnja (Poznańskie Studia Slawistyczne, 2015)
In this paper we (re-)examine the role of deliberate metaphors in the public discourse. Based on an analysis of metaphorical comments to the articles reporting on a dispute between the Croatian Prime Minister and Minister of Finance, we argue that in addition to a number of established discursive functions, metaphor may perform a therapeutic function aiding commenters in working through their emotions. Our analyses of the course that comments take shows that they are not structured according to a usual turn-taking logic, but rather on the basis of the coherence of the emotions shared by the commenters. Moreover, the tripartite internal structure of the comments (identifying the critical event, running the blend, possibly offering a solution to the critical event) is aimed at symbolically delegitimizing politicians, putting the author in charge of the experience, thus enabling him/her to work through it. Theoretically, such a view suggests that on the discourse level it is not necessarily metaphor that is used as the structuring device, but that emotion can structure metaphor.